The effect of chronic caffeine use on sporting performance in Division I collegiate baseball players - Foster, T.; Funderburk, L.; Pickler, M. C.; Bolden, L.; Lee, K. M.; Gallucci, A. (International Journal of Exercise Science Conference Proceedings, 2026)
Caffeine is a commonly used ergogenic aid and has been shown to improve acute athletic performance, such as speed, strength, and endurance. However, research exploring the effects of chronic caffeine use on sporting performance is limited, especially in Division I (DI) collegiate baseball players.